Impact of hybrid nanoparticle reinforcements on Mechanical properties of Epoxy-Polylactic Acid (PLA) Composites: Impact of hybrid nanoparticle reinforcements on Mechanical properties of Epoxy-Polylactic Acid (PLA) Composites (Fracture and Structural Integrity, 2024)
This study examines the influence of graphene nanoplatelets (GNPs) and multi-walled carbon nanotubes (MWCNTs) on the mechanical properties of SiO2-loaded epoxy-polylactic acid (PLA) composites. Epoxy and PLA were mixed to form the matrix with fillers, including SiO2, GNPs, and MWCNTs. The nanocomposites were prepared with a hybrid filler combination (SiO2/GNPs and SiO2/MWCNTs) with filler concentrations ranging from 0.1 – 0.4 wt. %. The composites were prepared using a combination of bath sonication and hand-casting techniques. They are characterized using tensile, bending impact, and fracture tests. The observed characteristics of GNP/SiO2 and MWCNTs/SiO2-loaded nanocomposites exhibited significant differences. Compared to the unmodified epoxy-PLA composite, incorporating 0.1 wt% of GNP/SiO2 filler improved tensile flexural and impact strength. Conversely, adding 0.4 wt% of MWCNTs/SiO2 filler enhances tensile, flexural, and impact strength. The dispersion mechanism of nanofillers was investigated using Scanning Electron Microscopy (SEM) on fracture surfaces obtained from tensile tests. An ANSYS workbench was used to simulate the impact of filler concentration on nanocomposites' tensile and bending strength, and a numerical analysis was performed.
Keywords: Hybrid Composites; Experimental testing; SEM analysis